Surgical adhesions among women undergoing laparoscopic gynecological surgery with or without adhesiolysis - prevalence, severity, and implications: retrospective cohort study at a University Hospital - Naser Al-Husban; Yousef Elayyan; Malab El-Qudah; Bayan Aloran; Rima Batayneh (SAGE Publishing, 2020)
Objective: To find out the prevalence of adhesions, severity, and their relation to the current clinical scenario and to the type of previous surgery. Methods and Materials: A retrospective study of patients who already had different previous abdominopelvic surgery and subsequently underwent gynecological laparoscopic surgery for various indications. The patients' clinical and operative notes were reviewed and analyzed. Results: There were 654 procedures performed. The most common indication for the laparoscopic surgery was secondary infertility 23.5%, followed by adnexal lesions 22.0% and primary infertility 19.6%. Intraoperative adhesions were found in 45.3%. Adhesions were deemed relevant to the clinical scenario in 21.3%. Patients who had a previous history of open (traditional) surgery were more likely to be found with adhesions in comparison with patients with history of laparoscopic surgery (odds ratio: 2.7, 95% confidence interval: 1.4-5.3, p  = 0.0025). The presence of adhesions was found to be strongly associated with previous abdominopelvic surgery than non-abdominopelvic surgery (odds ratio: 4.3, p  = 0.0078, 95% confidence interval: 1.5-12.5). The most common location of the adhesions was abdominal (36.1%), mixed abdominal and pelvic (35.1%), and pelvic adhesions (28.1%). Severe adhesions were found in 36.1%; 13.6% of converted laparoscopy to open surgery was due to adhesions. Cesarean sections were significantly associated with adhesions. Patients who had cesarean sections were more likely to have adhesions than those who had not (odds ratio: 5.7, 95% confidence interval: 3.8-8.6, p < 0.0001). Adhesiolysis was done without complications in 19.6% of patients with adhesions. Conclusion: Adhesions were prevalent in gynecological patients with previous abdominopelvic surgery. They were a significant contributor to the gynecological and reproductive issues. To minimize the risk of postoperative adhesions, laparoscopic approach should be encouraged instead of traditional surgery and rates of cesarean section should be reduced. Further high-quality studies are needed to establish conclusion and practical guidance toward the use of adhesion barriers.